(E)-Methyl 3-(2-methyl-1-phenylsulfonyl-1H-indol-3-yl)but-2-enoate - M. N. Ponnuswamy; A. K. Mohanakrishnan; G. Gobi Rajeshwaran; M. Thenmozhi; T. Kavitha (Acta Crystallographica Section E, 2009)
In the title compound, C20H19NO4S, the indole ring system is planar [r.m.s. deviation = 0.023 (2) Å]. The sulfonyl-bound phenyl ring is almost perpendicular to the indole ring system [dihedral angle = 86.75 (7)°]. The ester group is almost planar (r.m.s. deviation = 0.030 Å) and is oriented at an angle of 62.53 (5)° with respect to the indole ring system. Molecules are linked into a two-dimensional network parallel to the ab plane by intermolecular C—H...O hydrogen bonds.